Evaluation of anti-inflammatory and immunomodulatory potential of Lawsone (2-hydroxy-1,4-naphthoquinone) using pre-clinical rodent model of rheumatoid arthritis - Sattar, Sara; Shabbir, Arham; Shahzad, Muhammad; Akhtar, Tasleem; Anjum, Syed Muneeb; Bourhia, Mohammed; Nafidi, Hiba-Allah; Bin Jardan, Yousef A.; Dauelbait, Musaab; Mobashar, Aisha (Frontiers in Pharmacology, 2023)
Lawsone (2-hydroxy-1,4-naphthoquinone) is naturally present in Lawsonia Inermis and flowers of Eicchornia crassipes. This study assessed the anti-arthritic potential of Lawsone, using FCA-induced Sprague-Dawley rats. Arthritic progress was analyzed through a macroscopic scoring scale, measurement of paw edema, and histopathological changes.Effects of Lawsone on mRNA expression levels of inflammatory markers were examined using the reverse transcription PCR technique. ELISA technique was used to evaluate the PGE2 levels. Moreover, levels of biochemical and hematological parameters were also analyzed. The research elucidated that Lawsone showed an inhibitory potential towards arthritic progress and ameliorated the paw edema. The histopathological analysis also validated the inhibition in arthritic development. Treatment with Lawosne reduced the expression levels of inflammatory markers in rats i.e., VEGF, TNF-α, MMP-2, MMP-3, NF-κB, IL-1β, and IL-6. PGE2 levels (all p<0.001) were also found reduced in treatment groups.Lab investigations showed improved results of hematological and hepatic parameters in the treated groups as compared to the positive control. This study found no hepatotoxic or nephrotoxic effects of Lawsone in the test doses. Lawsone possesses an anti-arthritic property which could be ascribed to its immunomodulatory and anti-inflammatory effects.